Correlation between low skeletal muscle index and 3D anthropometric data measured by 3D body scanner: screening sarcopenia - Kim, Kyu Wan; Park, Yongsoo; Lee, Yohan; Cho, Minjoon (Frontiers in Medicine, 2024)
Background: The screening tools for sarcopenia are measuring calf circumference, SARC-F or SPPB. However, not all of these tools have high sensitivity, specificity, and low margins of error. This research investigates potential of 3D anthropometry of the lower extremities on screening of sarcopenia. Methods: From October 2022 to February 2023, we retrospectively analyzed results of 3D body scanner and bio-impedance analysis for patients aged 45 to 85 at risk of sarcopenia. The 3D scanner measured the surface and volume values of both thighs and calves. When skeletal muscle index (SMI) is less than 5.7, patients were classified to Low SMI group, indicative of sarcopenia. Results: A total six out of 62 patients were classified to Low SMI group, showing significantly lower values of right, left, mean calf volumes and mean calf surface than the other patients (right calf volume 2.62L vs 3.34L, p=0.033; left calf volume 2.62L vs 3.25L, p=0.044; mean calf volume 2.62L vs 3.29L, p=0.029; mean calf surface 0.12m2 vs 0.13m2, p=0.049). There was no statistical difference in thigh volume and surface. Through AUC-ROC analysis, mean calf volume was the most significant cut-off value (right calf volume 2.80L, AUC=0.768; left calf volume 2.75L, AUC=0.753; mean calf volume 3.06L, AUC=0.774; mean calf surface 0.12m2, AUC=0.747). Conclusion: The calf volume and surface values have significant relationship with low SMI, and the mean calf volume was the most significant cut-off screening value for Low SMI. The 3D scanner demonstrated its value as a new means for screening sarcopenia.